2018
DOI: 10.1371/journal.pone.0202435
|View full text |Cite
|
Sign up to set email alerts
|

Handling by avian frugivores affects diaspore secondary removal

Abstract: The balance between the costs and benefits of fleshy fruit production depends on the feeding behavior of their seed dispersers, which might effectively disperse seeds to farther areas or drop beneath parent plants some diaspores they handle during frugivory bouts. Nevertheless, the consequences of variation in fruit handling by primary seed dispersers on the secondary removal of diaspores remains poorly understood. We conducted a field study to determine how variation in fruit handling by avian frugivores affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
1
22
0
1
Order By: Relevance
“…In fact, it is sustained by the significant differences found between treatments (vertebrate-exclosure vs. control) in both preserved and disturbed sites, with higher removal rates for all species in the control treatment, meaning that vertebrates do remove between 5% and 16% of diaspores depending on site type and plant species. Guerra et al (2018) showed that vertebrates can be important as secondary seed dispersers and seed predators in campo rupestre. Therefore, these results call for con- The predominance of short dispersal distances (<5 cm) in our experiments are in accord with evidence showing ants as short-distance seed dispersers (Camargo, Martins, Feitosa, & Christianini, 2016, Christianini & Oliveira, 2010Gómez & Espadaler, 2013;Guerra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is sustained by the significant differences found between treatments (vertebrate-exclosure vs. control) in both preserved and disturbed sites, with higher removal rates for all species in the control treatment, meaning that vertebrates do remove between 5% and 16% of diaspores depending on site type and plant species. Guerra et al (2018) showed that vertebrates can be important as secondary seed dispersers and seed predators in campo rupestre. Therefore, these results call for con- The predominance of short dispersal distances (<5 cm) in our experiments are in accord with evidence showing ants as short-distance seed dispersers (Camargo, Martins, Feitosa, & Christianini, 2016, Christianini & Oliveira, 2010Gómez & Espadaler, 2013;Guerra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Guerra et al (2018) showed that vertebrates can be important as secondary seed dispersers and seed predators in campo rupestre. Therefore, these results call for con- The predominance of short dispersal distances (<5 cm) in our experiments are in accord with evidence showing ants as short-distance seed dispersers (Camargo, Martins, Feitosa, & Christianini, 2016, Christianini & Oliveira, 2010Gómez & Espadaler, 2013;Guerra et al, 2018). The majority of species observed are small ant species, suggesting that disperser body size is a key trait determining the outcomes of ant-plant interactions (Magalhães et al, 2018;Warren & Giladi, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodríguez-Pérez et al 2005; Reid and Armesto 2011; Haurez et al 2018) and in post-dispersal interactions with seed predators and secondary dispersers (e.g. Fricke et al 2016; Pan et al 2016; Guerra et al 2018).…”
Section: Where Are We Now and Where Do We Need To Go?mentioning
confidence: 99%
“…Overall, the ants can benefit plants on diaspore dispersal in many ways such as by the number of diaspores removed, diaspore removal distance and diaspore fate (Giladi , Leal et al , Griffiths et al , Fernandes et al ). However, the magnitude of these benefits is conditioned by several factors, both biotic and abiotic (Manzaneda et al , Gallegos et al , Guerra et al , Magalhães et al ). We can highlight four main factors that can directly affect the number of diaspores removed by ants, which include ant body size, diaspore size, plant growth form and habitat features.…”
Section: Introductionmentioning
confidence: 99%